2000
DOI: 10.1212/wnl.54.7.1448
|View full text |Cite
|
Sign up to set email alerts
|

Antisulfatide antibodies in neuropathy

Abstract: Antisulfatide antibodies are associated with several subtypes of peripheral neuropathy. Predominantly sensory or sensorimotor axonal neuropathies are most common in this series, with the sensory component either small fiber or mixed fiber type. A smaller demyelinating group indistinguishable from patients with chronic inflammatory demyelinating polyradiculopathy was also seen. One third of patients had a concomitant IgM monoclonal gammopathy, and approximately one half had elevated serum IgM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 23 publications
1
35
2
1
Order By: Relevance
“…72 Several studies have suggested a correlation between high titers of anti-sulfatide antibody and peripheral neuropathy. 56,57,[73][74][75] Additionally, a previous study highlighted the association of high titers of the antibody with predominantly sensory or sensorimotor axonal neuropathies. Reportedly, IgM monoclonal gammopathy and elevation of IgM are often observed in anti-sulfatide antibody-positive patients.…”
Section: Other Glycolipid Antibodiesmentioning
confidence: 96%
See 1 more Smart Citation
“…72 Several studies have suggested a correlation between high titers of anti-sulfatide antibody and peripheral neuropathy. 56,57,[73][74][75] Additionally, a previous study highlighted the association of high titers of the antibody with predominantly sensory or sensorimotor axonal neuropathies. Reportedly, IgM monoclonal gammopathy and elevation of IgM are often observed in anti-sulfatide antibody-positive patients.…”
Section: Other Glycolipid Antibodiesmentioning
confidence: 96%
“…Reportedly, IgM monoclonal gammopathy and elevation of IgM are often observed in anti-sulfatide antibody-positive patients. 75 Although anti-sulfatide antibody-associated neuropathies are relatively heterogeneous, the antibody might be related to IgM paraproteinemic neuropathies rather than CIDP. It is assumed that the IgM M-protein that reacts with sulfatide also reacts with sulfated glucuronyl paragloboside.…”
Section: Other Glycolipid Antibodiesmentioning
confidence: 99%
“…Increased titers of immunoglobulin M (IgM) antibodies to sulfatide have often been reported in patients with immune mediated neuropathies [1] even if their diagnostic role remains controversial [2,3]. These antibodies were originally associated with axonal neuropathy and IgM monoclonal gammopathy [4] but were subsequently associated with different neuropathies including predominantly sensory and often painful axonal neuropathy, sensorimotor demyelinating neuropathy and small fiber neuropathy [5][6][7][8][9][10][11]. The reactivity was variably associated with IgM monoclonal gammopathy [4][5][6][7][8][9][10][11] and with a concomitant reactivity with myelin-associated glycoprotein (MAG) [4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…High titers of IgG anti‐GM1 Ab can be also detected in Guillain–Barré syndrome (GBS) and in acute motor axonal neuropathy (AMAN) (2, 8–10). High titers of IgM anti‐sulfatide Ab have been found in chronic painful axonal sensory PN, demyelinating sensorimotor PN associated with IgM monoclonal gammopathy of undetermined significance (MGUS) or Waldenström's disease (11–16), or small‐fiber sensory PN (16). On the other hand, low to moderate titers of both autoAb can be found in non‐immune‐mediated PN and in other neurological disorders, too (2, 7, 16).…”
mentioning
confidence: 99%
“…High titers of IgM anti‐sulfatide Ab have been found in chronic painful axonal sensory PN, demyelinating sensorimotor PN associated with IgM monoclonal gammopathy of undetermined significance (MGUS) or Waldenström's disease (11–16), or small‐fiber sensory PN (16). On the other hand, low to moderate titers of both autoAb can be found in non‐immune‐mediated PN and in other neurological disorders, too (2, 7, 16). The importance of these Abs for the diagnosis of autoimmune PN is still uncertain, especially if they are found at low to moderate titer in patients with idiopathic PN, without the typical features of MN or PN associated with IgM paraproteinemia.…”
mentioning
confidence: 99%